Pengaruh pemahaman pendidik tentang anak usia dini, kompetensi pendidik dan sarana prasarana terhadap kemampuan potensi anak pada PAUD An-Nuur Sleman tahun pelajaran 2013/2014 - Yuni Mulyaniasih (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2015)
The purpose of this study was to discover simultaneous and partial influences of educators’ knowledge on early childhood, educators’ competence, and facilities and infrastructures on potential skills of young children in Ann-Nuur ECD, Sleman, 2013-2014 school year. His study was a correlational study with a quantitative approach to generalize observations of educators’ lesson implementations to measure how far educators’ understanding influence young children’s potential skills. Educators’ competence and supports of facilities and infrastructures influence children’s potentials and the result which is generalized to data validity and reliability. Independent variables and dependent variables were distributed normally. Data analysis technique used instrument administered to educators and analyzed by Partial Correlation Analysis and Multiple Regression Analysis Techniques. The result of correlation test analysis of educators’ understanding of early childhood, educators’ competence, and facilities and infrastructures showed positive and significant relationship between independent variables and dependent variables